EU development policy and poverty reduction enhancing effectiveness - Hout, Wil 1961- (International political economy of new regionalisms series, 2007)
This inspiring collection analyzes the contribution of EU development policy to poverty reduction. It focuses on various aspects of the policy - trade, agriculture and food security, and modes of policy making and implementation - and covers three geographical areas in relation to Europe - Latin America, Asia and Africa/Middle East. The volume concludes with practical recommendations for improving EU development policy with a view to enhancing its effectiveness